SISTEM INFORMASI AKUNTANSI PENGGAJIAN PEGAWAI BERBASIS WEB DENGAN METODE ACCRUAL BASIS: SISTEM INFORMASI AKUNTANSI PENGGAJIAN PEGAWAI BERBASIS WEB DENGAN METODE ACCRUAL BASIS - Rizka Novika; Setiawan, Dwi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
The purpose of this research is to produce a computerized employee payroll information system where the employee payroll information system of PT. Gemah Makmur Sejahtera still uses a manual system. The preparation of reports that still use Microsoft Excel worksheets also takes a long time, besides that the manual preparation is also vulnerable to user negligence in recording it. In this study, to minimize negligence in recording, the author will apply the accrual basis recording method, where the recording of salary expenses is carried out when a transaction occurs. This research was arranged by research and development method. The Employee Payroll Information System at PT Gemah Makmur Sejahtera is an employee payroll information system designed using a research and development methodology with UML (Unified Modeling Language) tools, direct observations and interviews with related parties. which can make it easier for the salary calculation stage, automatic report preparation, and automatic salary slips, resulting in more effective and efficient information.